Language Skills in the Context of Homestay Promotion in the Cibiru Wetan Tourism Village, Bandung Regency - Yualita, Perla; Sajodin; Maelany, Rina (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
Language skills are communication skills that allow one to receive and convey ideas clearly and precisely. With language skills, it is possible to establish effective communication, develop thinking, and develop culture and relationships between people who live in harmony in one place of residence. Likewise, homestays offer accommodation for visitors to stay with residents in their residences. The homestay concept offers a personal living experience close to the culture and daily life of the local community. Tourists can get homeowner recommendations regarding tourist attractions, typical foods, and local activities. Therefore, the language skills of residents need to be trained and developed so that they can become tour guides optimally according to their capacity. Thus, this community service carries the title: Language Skills in the Context of Homestay Promotion in the Cibiru Wetan Tourism Village, Bandung Regency. The activity results showed an increase in residents' language skills by 40.74%, accompanied by positive responses from the training participants. The conclusion of this community service is that language skills are an essential part of developing the world of tourism, especially in promoting homestays and tourist attractions, typical food, and local life activities in the surrounding areas, so it is recommended that community service provide regular language skills training.